EFISIENSI DAN KEADILAN DALAM SISTEM KEUANGAN SYARIAH: ANALISIS KRITIS TERHADAP MODEL KONVENSIONAL - Arief Maulana; Mardhatillah Mardhatillah (Mukhtasab: Journal of Economics and Islamic Business, 2025)
This article critically examines the relationship between efficiency and justice in the Islamic financial system and how both values are implemented within modern financial institutions. From an Islamic perspective, efficiency is not merely measured by profitability and productivity but by the extent to which economic activities promote social welfare and balance. The principle of justice (al-‘adl) serves as the moral foundation that distinguishes Islamic finance from the conventional system, which often prioritizes profit over ethics. This study employs a qualitative library research approach, analyzing scholarly literature and Islamic financial regulations. The findings reveal that Islamic finance still faces significant challenges in balancing efficiency and justice, primarily due to the dominance of trade-based products (murabahah) and the limited application of profit-sharing systems (mudharabah and musyarakah). Structural reform through product innovation, governance enhancement, and digitalization guided by the maqasid al-shari‘ah framework is essential to make Islamic finance genuinely just, inclusive, and sustainable. Thus, efficiency and justice should not remain normative ideals but become concrete pillars in realizing equitable economic prosperity.